Особенности использования проблемного метода в системе образования - Тойымбетова, Д.С. (My University, 2016)
In the article the problem of activation opens up cognitive students of modern institution of higher learning, in particular, future teachers. Attention is accented on such method of educating, as a method of , method of "problem situation" the examples of his use are specified and led with the purpose of activation of cognitive activity of students
Keywords: problem method; thinking; activation; analysis,; educating